A New Approach for Finding The Coefficients and Roots of The Ehrhart Polynomial of A Cyclic Polytope With Some Properties - Fatema Ahmed Sadeq (Engineering and Technology Journal, 2011)
The aim of this work is to give a simple description of a cyclic polytope and a new approach for finding the coefficient of its Ehrhart polynomials using Pascal triangles. Theorem for concluding that the roots of a cyclic polytopes are negative is also given.